Pengaruh Budaya Organisasi dan Lingkungan Kerja terhadap Kinerja Karyawan - Edi Kurniawan (Iqtishodiyah : Jurnal Ekonomi dan Bisnis Islam, 2021)
This study aims to examine whether organizational culture and work environment have an effect on employee performance. The independent variables in this study are organizational culture and work environment, while the dependent variable is employee performance. The research was conducted on employees of the Darul Ulum Child Welfare Institution, totaling 52 respondents. This type of research is quantitative research. The data collection method used a questionnaire. Data analysis using multiple linear regression. The results showed that organizational culture and work environment had a significant positive effect on employee performance.